A study in vivo of adrenergic receptors in the rectum and in the internal anal sphincter of the cat. Issue 8 (August 1970) - Kerremans, R.; Penninckx, F.
Abstract : The smooth muscle sphincteric activity of the anus in cats is based on two distinct mechanisms: a typical anal component, characterized by anal slow pressure waves not related to spike potentials in the internal anal sphincter, and an intestinal-like pressure component related to spiking activity in the internal sphincter. Anal slow pressure waves are influenced by the activity of alpha excitatory receptors within the internal sphincter, whereas no conclusive data are available concerning the action of adrenergic beta receptors on this pressure component. Intestinal-like pressure waves and the correlated spiking activity in the internal anal sphincter are influenced by alpha and beta inhibitory adrenergic receptors. The rectal wall of the cat contains alpha and beta adrenergic receptors producing relaxation.